Ketogenic diets and Alzheimer’s disease - Klaus W. Lange; Katharina M. Lange; Ewelina Makulska-Gertruda; Yukiko Nakamura; Andreas Reissmann; Shigehiko Kanaya; Joachim Hauser (Food Science and Human Wellness, 2017)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by decline in cognitive functions and associated with the neuropathological hallmarks of amyloid β-peptide plaques and neurofibrillary tangles. Cerebral glucose uptake and metabolism deteriorate in AD and this hypometabolism precedes the onset of clinical signs in AD. The early decline in brain glucose metabolism in AD has become a potential target for therapeutic intervention. This has led to investigations assessing the supplementation of the normal glucose supply with ketone bodies which are produced by the body during glucose deprivation and can be metabolized by the brain when glucose utilization is impaired. The present review provides a synopsis of preclinical studies and clinical trials assessing the efficacy of ketogenic diets in the treatment of AD. Both the direct administration of ketone bodies and the use of high-fat, low-carbohydrate ketogenic diets have been shown to be efficacious in animal models of AD and clinical trials with AD patients. The mechanism underlying the efficacy of ketogenic diets remains unclear, but some evidence points to the normalization of aberrant energy metabolism. At present there is only limited evidence of the usefulness of ketogenic diets in AD. However, this dietary approach seems to be promising and deserves further clinical investigations.